Tuttle mealybug Brevennia rehi (Pseudococcidae) - Ian Stocks (EDIS)
The Tuttle mealybug, Brevennia rehi (Lindinger), is a pest of many grass species and occurs nearly worldwide, especially where rice and sugarcane are grown. Because Bermuda and zoysia are important lawn grasses, especially in the southern United States, infestation by Tuttle mealybug should be considered whenever dieback is noticed, especially if the grass blades show white wax or are sticky from honeydew secretion. Both Bermuda and zoysia lawns are commonly installed as sod or plugs, which provide a ready route for the spread of infestations should the pest control practices of the grower fail to maintain a pest-free production environment. This 3-page fact sheet was written by Ian Stocks, and published by the UF Department of Entomology and Nematology, April 2013.